2022
DOI: 10.1128/spectrum.02582-21
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into Gene Response of Diorcinol- and Rubrolide-Treated Biofilms of the Emerging Pathogen Stenotrophomonas maltophilia

Abstract: Combating Stenotrophomonas maltophilia biofilms in clinical and industrial settings has proven to be challenging. S. maltophilia is multidrug resistant, and occurrence of resistance to commonly used drugs as well as to antibiotic combinations, such as trimethoprim-sulfamethoxazole, is now frequently reported. It is therefore now necessary to look beyond conventional and already existing antimicrobial drugs when battling S. maltophilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Preparation of the The prenyl group plays an important role in the bioactivity of prenylated diresorcinols. For example, recent structural inspection and hierarchical clustering suggested that the prenyl group as a side chain substituent of diresorcinols is essential for the antibacterial activity [20].…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of the The prenyl group plays an important role in the bioactivity of prenylated diresorcinols. For example, recent structural inspection and hierarchical clustering suggested that the prenyl group as a side chain substituent of diresorcinols is essential for the antibacterial activity [20].…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated a loss of antibacterial activity associated with hydration of the C-5/C-6 butenolide exomethylene moiety in new rubrolides V and W recently isolated from a New Zealand Synoicum species . Barbosa et al evaluated rubrolides for herbicidal applications, while more recently, Gudzuhn et al evaluated rubrolides as biofilm inhibitors against the emerging MDR pathogen S. maltophilia associated with cystic fibrosis.…”
Section: Bioactive Metabolites From Algoa Bay Marine Ascidiansmentioning
confidence: 99%